Application of Susceptible - Infected - Recovered epidemiological modeling to the occurrence of COVID-19: a systematic literature review (Research, Society and Development, 2020)
The aim of this article is to analyze, through a systematic literature review, the application of the, SIR, Susceptible-Infected-Recovered epidemiological modeling in the pandemic scenario caused by SARS-CoV-2. A bibliographic survey of scientific productions through the PubMed interface, which is linked to the MEDLINE database, and by the Virtual Health Library, emphasizing findings that presented some reference to the SIR epidemiological model with comparisons, application to disease and criticism in the context of COVID-19. 151 documents were found and after reading and defining selection criteria, 7 articles were selected for further systematic and in-depth analysis. As a result of data collection, the following categories of analysis were identified: Target audience, aspects and contributions for the understanding of the disease, models used as references to articles, assessment and presentation of limitations and criticisms when using these models to capture data on COVID-19. It was evaluated that there is no conformity regarding the use of a more adequate mathematical model, and for the SIR model to be used, in this context, adaptations were suggested in order to obtain a more accurate result.